A Literature Review: Effects of Bariatric Surgery on Adolescents and Young Adults - Wagner-Bieleń, Natalia Katarzyna; Zwierzchowska, Martyna; Antoniak, Agata; Jocz, Anna Maria; Centkowska, Anna; Banaśkiewicz, Joanna Karina; Żyta, Aleksandra Maria; Dąbrowska, Gabriela Helena; Żmijewska, Maria Anna; Ziółkowski, Jakub (Quality in Sport, 2025)
Introduction and Purpose: The global rise in adolescent obesity presents a critical public health challenge. Bariatric surgery has emerged as a treatment option for adolescents with severe obesity, especially when conservative interventions fail. This section outlines the rationale for evaluating bariatric surgery outcomes in young patients. A Brief Description of the State of Knowledge: Studies show that bariatric surgery in adolescents leads to significant and sustained weight loss, resolution of comorbidities such as type 2 diabetes and hypertension, and improvements in quality of life. However, concerns remain about nutritional deficiencies, bone health, and psychological outcomes, highlighting the importance of careful patient selection and multidisciplinary follow-up. Conclusions: Bariatric surgery can be an effective intervention for adolescents with severe obesity, providing numerous health benefits when other treatments are unsuccessful. Long-term monitoring and ethical considerations are essential for optimizing outcomes and ensuring safety in this vulnerable population.